The different types of tactile maps for orientation and mobility: a reflection - Coutinho, Ana Paula Geraldo; Schmitt, Isabela Guesser; Casarin, Vanessa; Vergara, Lizandra Garcia Lupi (InfoDesign, 2024)
Tactile maps for orientation and mobility play a valuable role in enabling individuals with visual impairments to have improved mobility autonomy. These resources assist in spatial orientation, allowing for the prior recognition of space or a specific route. Considering the importance of these maps, this article seeks to identify the different typologies of tactile maps used in buildings and public open spaces in Brazil. To obtain this objective, the method of surveying and cataloging images indexed in the Google Images database. The data were treated through thematic analysis and content analysis. From the data, it was possible to relate the use of different typologies of maps in environments with differentiated uses. The results show that in public spaces that offer specific services, such as public transport terminals, simplified tactile maps represented by tactile routes are most commonly used. Tactile maps represented by floor plans are the most used in cultural or contemplative spaces, with museums and squares.